Linguistic reconstruction of Central Asian toponyms: Evidence from Eastern historical sources - Nurdauletova, Bibaisha; Kenbayeva, Ainur (Research Journal in Advanced Humanities, 2026)
Central Asia is a key region for the ethnogenesis and civilizational development of the Turkic peoples, yet its toponyms have a complex history shaped by centuries of migration and multilingual interaction. Drawing on a historical-etymological approach and the concept of topoformants, this study linguistically reconstructs the historical etymology of approximately 1,000 Central Asian toponyms based on a wide range of Eastern historical documents. The corpus was compiled through purposeful sampling from Eastern chronicles and corroborated by works of renowned Orientalists and Turkologists. The analysis helped reconstruct original forms, identify probable root languages, and explore semantic shifts caused by social and environmental changes. Toponyms were classified by geographic features and linguistic origin, revealing Iranian and Turkic layers, as well as Arab-Islamic influences. The study demonstrates that Central Asian toponyms are multilayered constructs reflecting complex historical and cultural contacts. By integrating various Eastern sources, the study fills the gap in the comparative analysis of regional toponymy, contributing to Turkic onomastics, and highlighting the role of toponyms in preserving collective heritage and strengthening solidarity among Turkic-speaking communities. The study offers valuable insights into the shared historical heritage of Central Asia and its significance for contemporary identity and cultural memory.